Discussion on Management-and-Control Mode for Precise Disposal of Construction and Demolition Waste. Issue 1 (August 2020) - Peng, Qiyun; Xi, Chenggang; Wang, Ning; Ren, Fumin
Abstract: Faced with the severe challenges brought by construction and demolition waste (CDW), it is urgent to explore a more reasonable and effective management-and-control mode to dispose CDW. By analyzing the current situation of CDW disposal in China, it is found that the extant measures are mainly for the purpose of during- and post-event supervision, and the key factor to improve the status of CDW disposal is the government's pre-planning for recycling purpose. In view of this, a government-led management-and-control mode for precise disposal of CDW is proposed. The mode is implemented by the government in advance to determine the target value of CDW recycling, and optimize the allocation of CDW generation-transport-disposal chain on the basis of meeting the requirements of resource compliance, with three characteristics (precise classification recycling and quantitative prediction, precise control of transportation quantity, and precise planning for resource allocation) and two operating modes ("target limit of mandatory recycling + optimal distribution" and "target limit of mandatory recycling + free decision"). To achieve this mode, a series of countermeasures are proposed from the aspects of formulating policies, planning aims, setting up institutions, and building a supporting system.